2004
DOI: 10.1007/s00259-004-1464-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative cholescintigraphy and bile abnormalities in patients with acalculous biliary pain

Abstract: Acalculous biliary pain has been related to gallbladder dysfunction that produces a gallbladder emptying defect-a condition which favours the development of lithiasis. It is therefore probable that microlithiasis is present in patients with gallbladder dysfunction. The aims of this study were to measure gallbladder emptying and investigate bile abnormalities in patients with acalculous biliary pain. In 92 consecutive patients, gallbladder emptying was assessed by quantitative cholescintigraphy (abnormal ejecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, it has been suggested that microlithiasis not detected by the standard imaging techniques might be an etiological factor in a subset of patients with idiopathic acute pancreatitis [15,16]. Reduced ejection fraction of the gallbladder may lead to the formation of microlithia [17]. This study offers possible implications for the management of idiopathic acute pancreatitis.…”
Section: Discussionmentioning
confidence: 90%
“…However, it has been suggested that microlithiasis not detected by the standard imaging techniques might be an etiological factor in a subset of patients with idiopathic acute pancreatitis [15,16]. Reduced ejection fraction of the gallbladder may lead to the formation of microlithia [17]. This study offers possible implications for the management of idiopathic acute pancreatitis.…”
Section: Discussionmentioning
confidence: 90%
“…The presence of microcrystals and white blood cells are the essentials of a “positive” duodenal aspirate analysis. 8,15,17,20,24,25,2931 …”
Section: Introductionmentioning
confidence: 99%